Combination effect of tamoxifen and ascorbic acid treatment on breast cancer cells (MCF-7) and cervical cancer cells (HeLa) - Hasmah Abdullah,; Norlida Mamat,; Nor Munirah Zakaria,; Nur Iman Fatihah Mohd Yunan,; Muhammad Irfan Noor Hisham,; Hermizi Hapidin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Breast cancer and cervical cancer are among the leading causes of death among women in the world. Even though chemotherapy is available as cancer treatment, the development of drug resistance in both cancer cells has reduced the efficacy of chemotherapeutic drugs in such treatment. The current study was aimed to evaluate the cell viability of human breast cancer cells, MCF-7, and cervical cancer cells, HeLa upon the combination treatment of ascorbic acid and tamoxifen. The cell viability was measured using the MTT assay, with an incubation period of 72 hours in a humidified CO2 incubator. The concentrations of tamoxifen and ascorbic acid that reduced 50% of the cell population (IC50) were determined from the dose-response curve. The IC50 concentration was used to determine the cell viability in the treated cells. CompuSyn software was used to evaluate the combined effects towards both cells upon treatment and the results were calculated as combination index (CI). The data were analyzed using GraphPad Prism (version 7). Statistical analysis was performed using an independent t-test. The IC50 values of tamoxifen and ascorbic acid on MCF-7 cells were 14.53 μg/ml and 15.8 μg/ml respectively, while the IC50 values of tamoxifen and ascorbic acid on HeLa cells were 11.09 μg/ml and 202.3 μg/ml respectively. The combination of tamoxifen and ascorbic acid exerted a greater growth reduction percentage in both cells compared to tamoxifen alone. The results indicated that ascorbic acid synergizes the cytotoxic effect of tamoxifen at lower concentrations towards MCF-7 cells with a CI less than 1. However, the combination of tamoxifen and ascorbic acid exerted an antagonistic effect in HeLa cells, with a CI more than 1.